Cloning and DNA sequencing of a RAPD marker linked to oidium heveae-resistance gene of Hevea - Shoucai Chen; Dongqiong Fu; Hanshuang Shao; Xueqin (Chinese Journal of Tropical Crops, 1994)
A RAPD marker, OPV-10 390, linked to the Oidium heveae-resistance gene of Hevea brasiliensis was cloned and its DNA sequence was determined. Nucleotide sequence analysis by DNASIS TM system indicates that the fragment was not all encoding sequence and had no conservative sequence of 5- flanking region and 3- flanking region, but a structure similar to exon and intron.
Keywords: Disease resistance; DNA sequencing; Gene cloning; Hevea brasiliensis; Oidium heveae; RAPD marker